2012
DOI: 10.4067/s0717-95022012000200049
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Variations of the Branches of the Brachial Plexus with Bilateral Connections between Ulnar and Radial Nerves

Abstract: SUMMARY:During routine dissection of the upper limbs of a Caucasian male cadaver, multiple variations of the branches of the brachial plexus were observed. On the left side, the musculocutaneous nerve was absent and the muscles of the anterior compartment of the arm were innervated by the median nerve. The median nerve was also formed from three roots viz; two from the lateral and one from the medial cord of the brachial plexus. On the right side, the musculocutaneous nerve contributed a long communicating bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(26 reference statements)
1
9
1
Order By: Relevance
“…Many such communications were reported earlier [9][10][11][12][13][14]. A communication between musculo-cutaneous nerve and median nerve may be present [7,15,16]. In the present study, no such communication was noted.…”
Section: Discussioncontrasting
confidence: 44%
“…Many such communications were reported earlier [9][10][11][12][13][14]. A communication between musculo-cutaneous nerve and median nerve may be present [7,15,16]. In the present study, no such communication was noted.…”
Section: Discussioncontrasting
confidence: 44%
“…Connection between some terminal branches of brachial plexus are numerous and frequently have been reported by some authors, but from the literature reviewed, we found only two cases of connection between radial and ulnar nerves in the arm that had been reported, one of them was unilateral and the other bilateral (Ozguner et al;Ajayi et al, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…Variations in the nerve supply of the coracobrachialis muscle have also been explained by authors as mentioned earlier in this report. [1,5,[8][9][10][11][12] Appropriate knowledge of these variations other than those quoted in classical text books is important from both medical and surgical aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The musculocutaneous nerve is found to be absent or sometimes the nerve does not pierce the coracobrachialis muscle. [1,[8][9][10] It may adhere for some distance to the median nerve and pass behind the biceps. Some fibers of the median nerve may run in the musculocutaneous nerve, leaving it to join their proper trunk; less frequently the reverse occurs, and the median nerve sends a branch to the musculocutaneous nerve.…”
Section: Introductionmentioning
confidence: 99%